Study on Indonesia Crude Palm Oil Exports to Six Main Destination Countries 2000-2021 - Jenflower, Maria; Susilo, Yuvensius Sri; Herawan, Jonathan Ersten (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This study aims to assess the impact and factors influencing Indonesian CPO exports to six main destination countries from 2000 to 2021. The variables analyzed include real GDP per capita in the destination countries, inflation rates in these countries, and international CPO prices over the same period. The analysis employs a Random Effect Model (REM) processed using Eviews-10. The urgency of this study is to evaluate the circumstances of the EU's deforestation law by examining the contribution of Indonesian CPO exports. The results indicate that real GDP per capita, inflation, and international CPO prices significantly affect the export value of CPO to these six countries during 2000-2021.